2015
DOI: 10.2147/ijwh.s74832
|View full text |Cite
|
Sign up to set email alerts
|

Intention toward the continuation of female genital mutilation in Bale Zone, Ethiopia

Abstract: BackgroundFemale genital mutilation (FGM) is a harmful traditional practice that is deeply rooted in Africa. It is associated with health complications and human rights violations. Research on intention for the continuation of FGM and the social determinants underpinning this practice are scarce. Therefore, this study intended to assess the intention of women toward the continuation of FGM among Bale Zone reproductive-age women.MethodsA community-based cross-sectional study design supplemented by qualitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
2
31
2
Order By: Relevance
“…These were matching with reasons found by Bogale et al; 2015 who conduct a community based cross sectional study among reproductive age women revels the main reasons of FGM was to get married, to get social acceptance, to safeguard virginity, and religious recommendations. 21 Another study by the same authors in 2014 showed the main reason of FGM was religion, safeguarding virginity, tradition, and social values were the major reasons for the perpetuation of this practice. 22 While (125.%) of mothers did not practicing female circumcision, because it is harmful practice (78.1%), no religious origin (12.5%) and affect girls education (9.6%), This is results lower than findings reported by Bogale et al in 2014 who report 26.7% of the respondents had intention for the continuation of FGM.…”
Section: Discussionmentioning
confidence: 99%
“…These were matching with reasons found by Bogale et al; 2015 who conduct a community based cross sectional study among reproductive age women revels the main reasons of FGM was to get married, to get social acceptance, to safeguard virginity, and religious recommendations. 21 Another study by the same authors in 2014 showed the main reason of FGM was religion, safeguarding virginity, tradition, and social values were the major reasons for the perpetuation of this practice. 22 While (125.%) of mothers did not practicing female circumcision, because it is harmful practice (78.1%), no religious origin (12.5%) and affect girls education (9.6%), This is results lower than findings reported by Bogale et al in 2014 who report 26.7% of the respondents had intention for the continuation of FGM.…”
Section: Discussionmentioning
confidence: 99%
“…The practice may be linked to maternal mortality in Ethiopia and it is considered as one of the major national problems affecting the socioeconomic development of the country [15]. Although the true magnitude of the problem and the nature of the successful interventions is not yet known in Ethiopia, there has been a drop in the prevalence rate over a relatively short time from 80 percent in 2000 to 74.3 in 2005 [14].…”
Section: Introductionmentioning
confidence: 99%
“…An explorative study about the continuation of FGC in Bale Zone revealed that 26.7% of the respondents had an intention for the continuation of FGC. Religion, safeguarding virginity, tradition, and social values were the major reasons for the continuation of the practice [15, 19]. Another study in Ethiopia revealed that the uncircumcised females and those who attended secondary-level education and above were not intended to continue the practice compared to those who were not able to read and write and circumcised females [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that 26.7% of the respondents had intention for the continuation of FGM. Religion, safeguarding virginity, tradition, and social values were the major reasons for the perpetuation of this practice [9]. Further study shows Prevalence of female genital mutilation among Muslim Kurdish women in Erbil city is very high and more than one third of the women support the practice and have intention to mutilate their daughters [10].…”
Section: Causes Of Fgmmentioning
confidence: 84%